Associations of Diabetes and Obesity with Risk of Abdominal Aortic Aneurysm in Men. (23rd February 2017) - Wang, Lu; Djousse, Luc; Song, Yiqing; Akinkuolie, Akintunde O.; Matsumoto, Chisa; Manson, JoAnn E.; Gaziano, J. Michael; Sesso, Howard D.
Abstract : Background. The associations of diabetes and obesity with the risk of abdominal aortic aneurysm (AAA) are inconclusive in previous studies. Subjects/Methods. We conducted prospective analysis in the Physicians' Health Study. Among 25, 554 male physicians aged ≥ 50 years who reported no AAA at baseline, 471 reported a newly diagnosed AAA during a mean of 10.4 years' follow-up. Results. Compared with men who had baseline body mass index (BMI) < 25 kg/m 2, the multivariable hazard ratio (HR [95% CI]) of newly diagnosed AAA was 1.30 [1.06–1.59] for BMI 25–<30 kg/m 2 and 1.69 [1.24–2.30] for BMI ≥ 30 kg/m 2 . The risk of diagnosed AAA was significantly higher by 6% with each unit increase in baseline BMI. This association was consistent regardless of the other known AAA risk factors and preexisting vascular diseases. Overall, baseline history of diabetes tended to be associated with a lower risk of diagnosed AAA (HR = 0.79 [0.57–1.11]); this association appeared to vary by follow-up time (HR = 1.56 and 0.63 during ≤ and >2 years' follow-up, resp.). Conclusion. In a large cohort of middle-aged and older men, obesity was associated with a higher risk, while history of diabetes tended to associate with a lower risk of diagnosed AAA, particularly over longer follow-up.